Biographisches Erzählen und digitale Medien - Schuster, Britt-Marie (Handbuch Biographie. Methoden, Traditionen, Theorien)
Keywords: Historische Medienlinguistik

Gegengemeinschaften bilden: Ein Beitrag zur linguistischen Geschichtsschreibung des Widerstands (1933–1945) - Schuster, Britt-Marie (Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Jahrbuch des Instituts für Deutsche Sprache 2021)
Keywords: Kommunikationsgeschichte

Äußerungen formelhaft kommentieren: Bauernkomödien als Quelle historischer Idiomatik - Schuster, Britt-Marie; Georgi, Christopher (Bauernkomödien des 17. Jahrhunderts als sprachhistorische Quellen)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Brief - Dang-Anh, Mark; Scholl, Stefan; Schuster, Britt-Marie (Im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

Flugblatt – Flugschrift - Schuster, Britt-Marie (Im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

From Pure Art to Sheer Luxury: Magazines as Ornamental Constellations and the Emergence of Aesthetic Capitalism in the Early Twentieth Century - Gretz, Daniela; Krause, Marcus (Periodical Formats in the Market)
The concept of ‘ornamental constellations’ introduced in the following article highlights the structural relationships of decorative elements and miscellaneous content in magazines and the importance of the reader’s perspective for their interpretation. ‘Ornamental constellations’ are considered one of the most important media devices of emerging aesthetic capitalism, as they produce economies of attention and affect and establish a visual connection between the basic concept of a magazine, its individual contributions, and the readership addressed, thus promoting a specific aesthetic lifestyle. Their respective staging value is illustrated by analysing two complementary magazines and their constellation techniques: the elitist art magazine Blätter für die Kunst with its ‘strategic arrangement’ of literary and programmatic contributions and the creation of ‘resonances’ between them and the popular sports and society magazine Sport im Bild with its hybridizing flow of texts, images, and advertisements. Despite all the differences, it becomes clear that these are two quite compatible projects within the framework of an emerging aesthetic capitalism: whereas the Blätter für die Kunst staged and materialized the idea of pure art as an exclusive aesthetic lifestyle, the Sport im Bild made the desired aesthetic way of life also attainable by non-artists (with enough money) by associating it with the idea of an aesthetic capitalism.
Keywords: General Medicine

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Aufwärtsstreben als Niedergang oder Variationen des Immergleichen. Zur Ästhetik der Serialität in Gottfried Kellers "Martin Salander" in der "Deutschen Rundschau" - Gretz, Daniela (Kellers Erzählen)

Medieneffekte und -reflexionen im Erstdruck von Theodor Fontanes "Stechlin" in "Über Land und Meer" - Gretz, Daniela (Fontanes Medien)

Ein Blick auf: Verstetigung und Transfer im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Abendroth, Sonja; Meusel, Sarah